Solve the quadratic equation by factoring.
x2 + 5x - 24 = 0. Here are the multiple choices: {-8, 1}
{-8, 3}
{8, -3}
{8, 3}

Question

Asked 4/10/2013 6:46:46 PM

Updated 7/25/2014 1:49:49 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/25/2014 1:49:49 PM]

Expert answered|Mae87|Points 0|

Question

Asked 4/10/2013 6:46:46 PM

Updated 7/25/2014 1:49:49 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/25/2014 1:49:49 PM]

Rating

3

x^2 + 5x - 24 = 0;

(x + 8)(x - 3) = 0;

x + 8 = 0; x = -8;

x - 3 = 0; x = 3

x = -8 or x = 3

(x + 8)(x - 3) = 0;

x + 8 = 0; x = -8;

x - 3 = 0; x = 3

x = -8 or x = 3

Added 7/25/2014 1:49:48 PM

This answer has been confirmed as correct and helpful.

Evaluate the algebraic expression for the given value or values of the variable(s).
x2 - 3(x - y);x = 6 and y = 2 **Weegy:** It simplifies to 12-18+6=0 (More)

Question

Expert Answered

Updated 7/5/2014 11:27:29 PM

1 Answer/Comment

x^2 - 3(x - y); x = 6 and y = 2

6^2 - 3(6 - 2)

= 36 - 3(4)

= 36 - 12

= 24

6^2 - 3(6 - 2)

= 36 - 3(4)

= 36 - 12

= 24

Added 7/5/2014 11:27:28 PM

This answer has been confirmed as correct and helpful.

Evaluate the algebraic expression for the given value or values of the variable(s).
3x - 4;x = -4 (Points : 2) Here are the multiple choices: -16
16
-8
8 **Weegy:**
3x - 4;x = -4;
3(-4) - 4 = -12 - 4 = -16
(More)

Question

Expert Answered

Updated 8/5/2014 10:58:08 PM

0 Answers/Comments

6x + 2; x = 2 **Weegy:**
6x + 2; x = 2;
6(2) + 2 = 12 + 2 = 14
(More)

Question

Expert Answered

Updated 8/5/2014 10:59:10 PM

0 Answers/Comments

Write the algebraic expression without parentheses.
-(-2 + 7y) . Here are the multiple choices: -2 + 7y
2 - 7y
14y
2 + 7y **Weegy:** -(-2 + 7y), the algebraic expression is: 2 - 7y (More)

Question

Expert Answered

Updated 7/15/2014 9:13:51 AM

0 Answers/Comments

Simplify the algebraic expression.
-3(2x - 5) - 4x + 8 . HERE ARE THE MULTIPLE CHOICES: -10x + 23
2x + 23
10x + 23
-10x - 7 **Weegy:**
-3(2x - 5) - 4x + 8,
-6x + 15 - 4x + 8
= -10x + 23
(More)

Question

Expert Answered

Updated 6/13/2014 11:02:08 AM

0 Answers/Comments

27,346,165

questions answered

There are no comments.